Enlargement of the aortic valve ring, surgical technics: prosthesis-patient mismacht" - Milvio B. Ramírez López; Horacio E. Pérez López; Angel M. Paredes Cordero; Nizahel Estévez Álvarez (ECIMED, 2014)
The purpose of this work is to demonstrate that the aortic  enlargements procedures, first described for patients with small aortic annulus, are reproducible with good results in patients with prosthesis-patient mismacht (effective orifice area < 0.85 cm2/m2). We made a synthesis of the different surgical procedures, its results and outcome, and report the results and experience of different authors.